2011
DOI: 10.2151/jmsj.2011-a02
|View full text |Cite
|
Sign up to set email alerts
|

The Cross-Equatorial Northerly Surge over the Maritime Continent and Its Relationship to Precipitation Patterns

Abstract: This study describes the characteristics of the cross-equatorial northerly surge (CENS), a northerly flow that appears intermittently over the equatorial region between October and April, and its relationship to the precipitation patterns over the Maritime Continent. The CENS in this study was defined as the area-averaged northerly wind exceeding 5 m s À1 over 105 E-115 E, 5 S-EQ based on the QuikSCAT sea surface wind data. During the 10 winters from December 2000 to March 2009, 62 CENS events were extracted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
68
0
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(85 citation statements)
references
References 33 publications
8
68
0
9
Order By: Relevance
“…3) showed that during 4−13 January, strong westerly winds > 10 m s −1 were observed from near the surface up to 400 hPa (~8 km), with maximum wind speed being at the 900600hPa layer, consistent with the passage of the strong active phase of the MJO over the Maritime Continent and the western Pacific regions. It is note worthy that the upper westerly winds continued over Java Island to a lower latitude and can even penetrate into the Southern Hemisphere (Wu et al 2007;Hattori et al 2011). A strong and persistent transequatorial monsoonal flow is a crucial factor in extremely heavy rain over western Java Island.…”
Section: Eastward Propagation Of An Active Phase Of the Mjo In Late Dmentioning
confidence: 99%
See 2 more Smart Citations
“…3) showed that during 4−13 January, strong westerly winds > 10 m s −1 were observed from near the surface up to 400 hPa (~8 km), with maximum wind speed being at the 900600hPa layer, consistent with the passage of the strong active phase of the MJO over the Maritime Continent and the western Pacific regions. It is note worthy that the upper westerly winds continued over Java Island to a lower latitude and can even penetrate into the Southern Hemisphere (Wu et al 2007;Hattori et al 2011). A strong and persistent transequatorial monsoonal flow is a crucial factor in extremely heavy rain over western Java Island.…”
Section: Eastward Propagation Of An Active Phase Of the Mjo In Late Dmentioning
confidence: 99%
“…The effects of the active phase of the MJO on the extreme precipitation event Hattori et al (2011) investigated the occurrence of cross equatorial northerly surge and its relation to precipitation over the Maritime Continent during the regional wet season from December to March for the 11 years from 1998 to 2009. Their results showed that during crossequatorial northerly surge events, enhanced precipitation is evident over the northern coast of Java Island and the Java Sea in both active and inactive MJO phases.…”
Section: Eastward Propagation Of An Active Phase Of the Mjo In Late Dmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the observation has conducted during the period of developed northerly cold surge in the Philippine Sea and the active phase of MJO convection over the Maritime Continent. In other words, it corresponds to the northerly surge/MJO combined pattern where the precipitation significantly increases over the Maritime Continent as shown in Hattori et al (2011).…”
Section: Analysis Error Reduction By the Kh Observationsmentioning
confidence: 97%
“…Moreover, the analysis indicated that the northerly surge greatly affects not only convective activity but also rainfall distributions in the tropics near the equator and over the Indonesian Maritime Continent in the Southern Hemisphere (Hattori et al 2011;Wu et al 2013;Pullen et al 2015). Hattori et al (2011) showed that the northerly surge/MJO (Madden-Julian Oscillation) combined pattern (16 cases) produced much greater precipitation over the Maritime Continent than either MJO (20 cases) or northerly surge (11 cases) alone. Love (1985) showed that the zonal pressure gradients near the equator induced by cold surges in the winter hemisphere influence the development of tropical cyclones (TCs) in the summer hemisphere.…”
Section: Introductionmentioning
confidence: 99%